Impact of Calorie Intakes on the Risk of Bronchopulmonary Dysplasia in Extremely Preterm Infants - Belal Alshaikh; Siddartha Buddhavarapu; Albert Akierman; Abhay Lodha; Reginald Sauve; Amuchou Soraisham (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2017)
Aim: To examine  whether  caloric  intake  during  the first  week of age influences the risk  of Bronchopulmonary Dysplasia (BPD) in extremely preterm infants. Methods: In this retrospective cohort study, all infants born with gestational age < 29 weeks over 30 months period were eligible for the study. Infants with major congenital anomalies and those who died before 36 weeks postmenstrual age were excluded. We compared the nutritional characteristics between infants who developed BPD and those without BPD. Results: Of the 262 eligible infants, 233 were included for the study. A total of 125 infants developed BPD. Infants with BPD had similar fluid intake in the first week of life to other infants with no BPD. After adjusting for gestational age, severity of illness and PDA, BPD was associated a trend towards reduced cumulative protein intake in the first week of life (OR=0.91 95% CI: 0.81-1.01). Increase time to reach full feed is associated with increased risk of BPD (OR=1.03; 95%CI: 1.00 - 1.06). Conclusions: In  preterm  infants  born  at  less  than  29  weeks,  provision  of  adequate  calorie  intake particularly protein in the first week of life may associate with decreased risk of BPD.